Earnings Management Trend in Manufacturing Companies Sub-Sector Food and Beverage Listed on the Indonesia Stock Exchange Year 2019-2023 - Efendi, Febian Dwi; Probowulan, Diyah; Zulkarnnaeni, Achmad Syahfrudin (Westscience Press, 2024)
This study aims to analyze the trend of earnings management in manufacturing companies operating in the food and beverage sub-sector listed on the Indonesia Stock Exchange. Earnings management trends encompass methods used by companies to manipulate or manage their financial statements. Factors influencing earnings management include tax planning, income tax expenses, and profitability. The management's goal is to enhance corporate earnings to reflect stable profits, thus accurately portraying the company's financial performance in future periods. The study population consists of 45 companies, with a sample of 9 companies selected using purposive sampling. Data collection utilized secondary data from quarterly financial reports of manufacturing companies listed on the Indonesia Stock Exchange from 2019 to 2023. The research employed descriptive analysis to assess earnings management trends as predictors of profit increases. The findings reveal significant fluctuations in earnings management practices among food and beverage manufacturing companies listed on the Indonesia Stock Exchange during the period from 2019 to 2023.